Istikhdām Wasīlah al-Sam’iyyah al-Syafawiyyah fī Ta’līm al-Lugah al-‘Arabiyyah li Tarqiyah Mahārah al-Istimā’ (Dirāsah Syibhu Tajribah li al-Ṣaff al-Khāmis bi Madrasah al-Ibtidāiyyah al-Islāmiyyah Maṭla’ al-Aṭfāl Cibiru Bandung): Using Audio Visual Media In The Arabic Learning To Increasing Listening Skill - abdul basit (Lisanul Arab: Journal of Arabic Learning and Teaching, 2024)
Listening skills (maharah istima') have an important role in language skills because listening is the first means of further language acquisition. On the other hand, in this modern era, the learning system is increasingly sophisticated, so teachers must always follow current developments so that the learning process is appropriate to current conditions. Learning media can be used as a solution so that learning can go according to plan and in the process students can be more enthusiastic and enthusiastic in teaching and learning activities. Among the learning media that can be used is audio visual media (sam'iyah syafawiyah) for Arabic listening skills in class 5 MI Matla'ul Atfal Cibiru Bandung. This research uses a quantitative quasi experimental design approach and a time series design model without a control group. The aim of this research is to determine the improvement in Arabic listening skills of grade 5 students at MI Matla'ul Atfal Cibiru Bandung using audiovisual learning media. Based on the results of research conducted, namely; Before the application of audiovisual media, students' listening ability was low (57; 56; 56.8), whereas after the application of audiovisual media it tended to increase (94; 92.8; 93.4). Therefore, it can be concluded that audio visual media is effective for learning Arabic listening skills in class 5 students at MI Matla'ul Atfal Cibiru Bandung and it is highly recommended that this learning media be used for learning Arabic listening skills in class 5 at other schools.